2013
DOI: 10.3391/ai.2013.8.3.12
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of the parasite Sphaerothecum destruens in the invasive topmouth gudgeon Pseudorasbora parva in the Netherlands, a potential threat to native freshwater fish

Abstract: The R/V Oceanus completed a 9,789 km, 28 day passage from Woods Hole, Massachusetts, in the Atlantic Ocean, through the Panama Canal to Yaquina Bay, Oregon, in the Pacific Ocean on 21 February 2012. The Oceanus had previously operated in the Mediterranean Sea and Atlantic Ocean (including the Caribbean Sea). We document the sequential acquisition of the barnacles Balanus trigonus and Amphibalanus venustus and the oyster Ostrea equestris on the Oceanus on its high and low latitude transoceanic, intra-oceanic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…However, these are unlikely to detect intra-cellular pathogens such as Sphaerothecum destruens that is hosted by P. parva . This pathogen has proved difficult to detect in wild populations, due to its size and the absence of disease or gross tissue damage, but is now increasingly being detected as molecular methodologies improve, with this resulting in the recent detection of its presence and distribution in countries such as the Netherlands (Spikmans et al 2013). This is important, given that this pathogen is associated with potentially substantial mortality rates in salmonid and cyprinid fishes (Andreou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, these are unlikely to detect intra-cellular pathogens such as Sphaerothecum destruens that is hosted by P. parva . This pathogen has proved difficult to detect in wild populations, due to its size and the absence of disease or gross tissue damage, but is now increasingly being detected as molecular methodologies improve, with this resulting in the recent detection of its presence and distribution in countries such as the Netherlands (Spikmans et al 2013). This is important, given that this pathogen is associated with potentially substantial mortality rates in salmonid and cyprinid fishes (Andreou et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similar low levels of prevalence and intensity of L. cyprinacea infection in P. parva to those in our study have been reported in the literature (Margaritov and Kiritsis, 2011). The above-mentioned parasite resistance actually refers to the resistance to the possible damaging effects of the parasite, the topmouth gudgeon being otherwise known as a healthy carrier for different parasite species (Spikmans et al, 2013) or being a host for Unonid glochidia, a relation which some authors define more as commensalism (phoresy) than parasitism (Douda et al, 2012). Secondly, we have a host-parasite combination, L. gibbosus and L. cyprinacea, which have lived in sympatry in Europe for more than 100 years, and a newly arrived host species population (P. parva).…”
Section: > Differences In Parasitological Parametersmentioning
confidence: 99%
“…It is known that one of the major threats for native biodiversity is the introduction of exotic species which can cause the extinction of endemic species (Simberloff, 2010;Smith et al, 2015). Several studies have reported the negative impact of P. parva on European fish species due to predation on the eggs and larvae of native species, inter-specific competition for food, and the introduction of non-native parasites (Welcomme, 1988;Gozlan et al, 2005;Pinder and Gozlan, 2005;Pollux and Korosi, 2006;Gozlan et al, 2010;Spikmans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%